THE EFFECT OF THE BLENDED LEARNING STRATEGY ON THE SOME TECHNICAL PERFORMANCE OF GYMNASTIC SKILLS FOR STUDENTS - Hassan, Ameen Atta (Universitas Negeri Jakarta, 2026)
Background. The importance of this research has emerged in its focus on blended learning to help students increase their motivation to learn, develop cognitive and performance skills, and meet their individual needs so that each student learns at their own pace. It also increases their sense of equality in educational opportunities. Objectives. The purpose of this paper is to design an educational program using a blended learning strategy and to determine its impact on students' gymnastic skill performance. Method. The researcher used the experimental method, given its suitability for the nature of this research, adopting a single-group experimental design with pre- and post-tests. After conducting the pre-tests and entering the data into Excel, the researcher implemented the main experiment on the research sample for 12 weeks, with two units per week. After completing the main experiment, the post-tests were conducted, and the data were entered into Excel. This data was processed using the SPSS statistical package. Results. The total average arithmetic mean for the regular physical education lesson is (1.79), and the total average arithmetic mean for the physical education lesson with applications of the blended learning strategy is (2.96). Conclusion. There are statistically significant differences between the average pre- and post-tests of the experimental group regarding gymnastic skill performance, in favor of the post-test.